Strengths and weaknesses in reading skills of youth with intellectual disabilities - Channell, Marie Moore (Res Dev Disabil, 2012)
Reading-related skills of youth with intellectual disability (ID) were compared with those of typically developing (TD) children of similar verbal ability level. The group with ID scored lower than the TD group on word recognition and phonological decoding, but similarly on orthographic processing and rapid automatized naming (RAN). Further, phonological decoding significantly mediated the relation between group membership and word recognition, whereas neither orthographic processing nor RAN did so. The group with ID also underperformed the TD group on phonological awareness and phonological memory, both of which significantly mediated the relation between group membership and phonological decoding. These data suggest that poor word recognition in youth with ID may be due largely to poor phonological decoding, which in turn may be due largely to poor phonological awareness and poor phonological memory. More focus on phonological skills in the classroom may help students with ID to develop better word recognition skills.